‘The happy effect of my writing’: Richardson’s Plotting and Epistolary Theory - Essig García, Daniel (Estudios Ingleses de la Universidad Complutense, 2012)
The article explores an alternative genealogy for Richardson’s novel of sensibility, and looks at the practice of reading in sentimental novels. Richardson cannot be properly understood if one does not take into account the political culture of his time, including misrepresentation and manipulation of the public. The centre of the article is a discussion of the volte-face scene in Pamela (published in 1740), managed masterfully by Samuel Richardson as plotter. In that scene, the two protagonist bodies are brought to accord and harmony by a reciprocal activity of reading: the interaction of those bodies, in the theatre of reading, leads to an effusion of sentiment and sensibility, which is the decisive factor in moralizing the masculine character, redeemed from rake to model husband, and become the mouthpiece of a new ethos for the 18th century British gentry.